Antibacterial ceramic glaze and preparation method thereof
By reasonably proportioning bentonite, potassium feldspar, quartz and other materials in ceramic glaze, and adding nanotitanium nitride and lanthanum cobaltate microspheres, the problem that the antibacterial properties and thermal stability of the existing antibacterial ceramic glaze are difficult to reach the ideal state after high-temperature calcination, and ceramic materials with high-efficiency antibacterial and excellent thermal shock resistance are achieved.
Patent Information
- Application Number
- CN202410724113.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2044-06-05
AI Technical Summary
The antibacterial performance and thermal stability of existing antibacterial ceramic glazes are difficult to reach the ideal state after high-temperature calcination, and have poor thermal shock resistance and cannot withstand rapid temperature changes.
By reasonably proportioning bentonite, potassium feldspar, quartz, barium carbonate, aluminum hydroxide, zircon, titanium nanonitride, lanthanum cobaltate microspheres and antibacterial additives, and using ball milling to ensure uniform mixing and fine particle size of the raw materials, an antibacterial ceramic glaze with uniform performance was prepared.
After high-temperature calcination, ceramic materials with high-efficiency antibacterial effects and excellent thermal shock resistance are formed, and excellent antibacterial ability under light conditions, improving the thermal stability and thermal shock resistance of the glaze.
Smart Images

Figure BDA0004878087900000091 
Figure BDA0004878087900000101 
Figure BDA0004878087900000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic glazes, and in particular to an antibacterial ceramic glaze and a preparation method thereof. Background Art
[0002] Ceramic glaze is a liquid or paste-like substance coated on the surface of ceramics. Its main components include oxides and glass components. It can form a hard and shiny coating during the firing process, protecting the surface of the object and enhancing its decorative effect and beauty. Ceramic glaze has many types, such as colorless transparent glaze, colored glaze, etc., which are widely used in tableware, kitchenware, decorations and other fields.
[0003] In recent years, with the development of science and technology and the improvement of health awareness, antibacterial ceramic glazes have gradually become popular. People hope to reduce bacterial growth and improve the hygiene and safety of the living environment through them. The increasing attention paid to the antibacterial properties of ceramic glazes has also prompted ceramic companies and professional glaze companies to re-examine the preparation process of ceramic glazes, and to optimize the preparation process by changing the raw material ratio and other methods to improve the quality of ceramic glazes. However, most of the current improvement methods are limited to changing the type and ratio of raw materials. In actual use, the antibacterial properties and thermal stability of the prepared ceramic glazes are difficult to achieve the ideal state. Therefore, designing a new ceramic glaze preparation process that has stable antibacterial properties and thermal stability has become a technical problem that needs to be solved urgently.
[0004] CN116589184B discloses a ceramic glaze and its preparation process. The invention loads silver ions on the surface of nano zinc oxide, which can not only make the glaze have the antibacterial properties of silver ions, but also improve the anti-glaze cracking performance of the glaze through the action of silver-loaded nano zinc oxide. Combined with the addition of sodium hexametaphosphate, the silver-loaded nano zinc oxide can be better dispersed in the glaze, thereby reducing the cracking probability of the ceramic glaze after glazing. In addition, the invention also adds gold tailings and composite stabilizers to the raw materials of the glaze. Although the glossiness of the glaze and the thermal stability of the glaze are improved to a certain extent, the thermal stability test of the glaze only passes the heat exchange temperature test from 180°C to 20°C, and the thermal stability is poor.
[0005] CN113860734B discloses a ceramic glaze with antibacterial function and its preparation method and application. The ceramic glaze is prepared by adding a carrier to an acid solution and mixing to obtain a suspension solution; mixing the acid solution, the alkaline solution and water to obtain a mixed solution; then mixing the suspension solution and the mixed solution, and adding a soluble zinc salt, a soluble scandium salt and a soluble neodymium salt thereto, calcining after mixing to obtain a composite antibacterial agent; finally, mixing the base glaze and the composite antibacterial agent and grinding them to prepare the ceramic glaze. Although the ceramic glaze of the invention can still maintain excellent antibacterial properties and glaze quality under the firing conditions of daily ceramic firing temperature of 1280-1350°C and firing time of 8-10h, the ceramic glaze has poor thermal shock resistance and cannot withstand rapid temperature changes. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the present invention provides an antibacterial ceramic glaze and a preparation method thereof, which can form a ceramic material with high-efficiency antibacterial effect and excellent thermal shock resistance after high-temperature calcination, and exhibits excellent antibacterial ability under light conditions.
[0007] One of the purposes of the present invention is to provide a method for preparing an antibacterial ceramic glaze, comprising the following steps:
[0008] (1) mixing bentonite, potassium feldspar, quartz, barium carbonate, aluminum hydroxide and zircon uniformly, adding the mixture into a ball mill, ball milling and sieving to obtain a ceramic glaze base material;
[0009] (2) dispersing lanthanum cobaltate microspheres in water, ultrasonically treating the mixture, and then adding an antibacterial additive and stirring for 10-12 hours to obtain a mixture; mixing the nano-titanium nitride and the mixture evenly and adding the mixture to a ball mill for ball milling; then adding a ceramic glaze base material, adjusting the slurry specific gravity with water, and continuing ball milling to obtain an antibacterial ceramic glaze.
[0010] Preferably, the weight ratio of each raw material component is:
[0011] 25-35 parts of bentonite, 25-35 parts of potassium feldspar, 15-20 parts of quartz, 5-8 parts of barium carbonate, 3-5 parts of aluminum hydroxide, 8-10 parts of zircon, 1.5-3 parts of nano titanium nitride, 2-5 parts of lanthanum cobaltate microspheres, and 0.3-1 part of antibacterial additives.
[0012] Preferably, the method for preparing the lanthanum cobaltate microspheres comprises the following steps, measured by weight:
[0013] 0.14-0.3 parts of lanthanum nitrate (III) hexahydrate, 0.1-0.2 parts of cobalt nitrate (II) hexahydrate and 35-45 parts of isopropanol are mixed and stirred for 30-40 minutes until the mixture is uniformly mixed, and then 6-10 parts of propylene glycol are added and ultrasonically treated for 30-40 minutes to obtain a mixed solution; the mixed solution is transferred to a polytetrafluoroethylene liner and placed in a hydrothermal reactor to react at 170-200° C. for 6-10 hours; after the reaction is completed and naturally cooled, the obtained sample is centrifuged at 6000-8000 rpm for 5-10 minutes, the solid is collected, washed, and then dried at 55-65° C. for 10-15 hours; finally, the dried material is calcined and kept warm at 650-750° C. for 2-3 hours to obtain lanthanum cobaltate microspheres.
[0014] Preferably, the antibacterial additive is selected from one of nano zinc oxide, nano silver powder and nano titanium dioxide.
[0015] Preferably, in the step (1), the ball milling is performed at a ball milling speed of 150-250 r / min for 3-5 h; and the sieving is performed through a 300-400 mesh sieve.
[0016] Preferably, in step (2), the temperature of ultrasonic treatment is 40-60°C, the ultrasonic frequency is 30-50KHz, the ultrasonic power is 300-400W, and the time is 30-50min.
[0017] Preferably, in step (2), the nano-titanium nitride and the mixture are mixed evenly and then added to a ball mill for ball milling at a ball milling speed of 250-350 r / min for 1-2 h.
[0018] Preferably, in step (2), a ceramic glaze base material is added, the slurry specific gravity is adjusted to 1.2-1.6 with water, and the ball milling is continued at a ball milling speed of 250-350 r / min for 25-30 hours.
[0019] The second object of the present invention is to provide an antibacterial ceramic glaze prepared by the above method.
[0020] The bentonite in the present invention is a hydrated layered silicate mineral, which can improve the plasticity and bonding of the glaze and help form a smooth and uniform glaze surface.
[0021] In the present invention, potassium feldspar is a common flux in glaze, which can reduce the melting point of glaze and improve the fluidity of glaze, thus facilitating the uniform distribution of glaze on the ceramic surface.
[0022] The quartz in the present invention increases the hardness and wear resistance of the glaze, and its stability at high temperatures helps to improve the thermal stability of the glaze.
[0023] In the present invention, barium carbonate can be used as a flux for glazes to reduce the firing temperature of the glazes and may also help to improve the glossiness of the glazes.
[0024] In the present invention, the aluminum hydroxide helps to improve the chemical stability and mechanical strength of the glaze, and the water vapor generated by its decomposition may help the sintering process of the glaze.
[0025] The zircon in the present invention can improve the wear resistance and corrosion resistance of the glaze, and at the same time it has high thermal stability, which helps to improve the thermal shock resistance of the glaze.
[0026] Nano titanium nitride in the present invention may enhance the mechanical properties and heat resistance of the glaze due to its high melting point and good chemical stability, and nano titanium nitride itself has a low thermal expansion coefficient. When mixed with zircon under high temperature calcination conditions, it may introduce lattice distortion in the crystal structure of zircon to form a composite material with a lower thermal expansion coefficient, which can effectively reduce the volume expansion of the material when the temperature changes, reduce the internal stress caused by rapid temperature changes, and improve the thermal shock resistance of the glaze. In addition, nano titanium nitride, as a material with local surface plasma resonance characteristics, may enhance the antibacterial effect of lanthanum cobaltate microspheres and improve the overall antibacterial properties of the glaze through synergistic effects.
[0027] Beneficial effects of the present invention:
[0028] 1. Compared with the prior art, the present invention provides an antibacterial ceramic glaze, which reasonably mixes bentonite, potassium feldspar, quartz, barium carbonate, aluminum hydroxide, zircon, nano titanium nitride, lanthanum cobaltate microspheres and antibacterial additives, and through ball milling, ensures the uniform mixing and fine particle size of the raw materials, thereby preparing an antibacterial ceramic glaze with uniform performance. The ceramic glaze prepared by the present invention can form a ceramic material with high-efficiency antibacterial effect and excellent thermal shock resistance after high-temperature calcination, and exhibits excellent antibacterial ability under light conditions.
[0029] 2. The present invention prepares lanthanum cobaltate microspheres with a porous structure by a simple solvent thermal method, and mixes the lanthanum cobaltate microspheres with antibacterial additives such as nano zinc oxide, nano titanium dioxide, and nano silver powder after ultrasonic treatment, and then adds nano titanium nitride and ceramic glaze base materials for mixed ball milling to obtain antibacterial ceramic glaze. The lanthanum cobaltate microspheres and nano titanium nitride are mixed and used to effectively avoid the problem of nano titanium nitride agglomeration during high-temperature calcination, reduce its adverse effects on the thermal shock resistance of ceramic materials, and improve its thermal stability. At the same time, the antibacterial additives and lanthanum cobaltate microspheres are used in coordination to form a complex with a new crystal structure during high-temperature calcination, which not only broadens the light absorption range of the complex, enhances the light response ability, and enhances the photocatalytic antibacterial activity of the complex, but also improves the thermal stability of the complex, avoids the antibacterial activity of the antibacterial additives due to high temperature decomposition or ion loss, and increases the antibacterial activity of the antibacterial additives at high temperatures. DETAILED DESCRIPTION
[0030] Parameters for specific chemical substances used, sources.
[0031] Nano-titanium nitride, item number, AM-TiN-072-1, particle size: 30 nm, purchased from Zhejiang Yamei Nanotechnology Co., Ltd.;
[0032] Nanosilver powder, CAS number: 7440-22-4, size: 60 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0033] Nano zinc oxide, product number: TZP-50, particle size: 30 nm, purchased from Jiangsu Tianxing New Materials Co., Ltd.;
[0034] Nano-titanium dioxide, CAS number: 13463-67-7, model: J25, particle size: 30 nm, was purchased from Xuancheng Jingrui New Materials Co., Ltd.
[0035] Example 1
[0036] A method for preparing an antibacterial ceramic glaze comprises the following steps:
[0037] (1) 30 parts by weight of bentonite, 28 parts by weight of potassium feldspar, 16 parts by weight of quartz, 6 parts by weight of barium carbonate, 3.5 parts by weight of aluminum hydroxide, and 9 parts by weight of zircon are mixed and added into a ball mill, and the mixture is ball milled at a ball mill speed of 200 r / min for 4 h, and passed through a 300-mesh sieve to obtain a ceramic glaze base material;
[0038] (2) Dispersing 3 parts by weight of lanthanum cobaltate microspheres in 10 parts by weight of water, ultrasonically treating the mixture for 40 min at a temperature of 50°C, an ultrasonic frequency of 40 kHz, and an ultrasonic power of 350 W, then adding 0.5 parts by weight of nano-silver powder and stirring for 11 h to obtain a mixture; after uniformly mixing 2 parts by weight of nano-titanium nitride and the mixture, adding the mixture to a ball mill and milling the mixture at a ball mill speed of 300 r / min for 1.5 h; then adding a ceramic glaze base material, adjusting the slurry specific gravity to 1.4 with water, and continuing ball milling for 26 h to obtain an antibacterial ceramic glaze.
[0039] The method for preparing lanthanum cobaltate microspheres in step (2) comprises the following steps:
[0040] 0.223 parts by weight of lanthanum nitrate (III) hexahydrate, 0.15 parts by weight of cobalt nitrate (II) hexahydrate, and 40 parts by weight of isopropanol were mixed and stirred for 35 minutes until they were uniformly mixed, and then 8 parts by weight of propylene glycol were added, and ultrasonic treatment was performed for 35 minutes at a temperature of 40°C, an ultrasonic frequency of 40KHz, and an ultrasonic power of 300W to obtain a mixed solution; the mixed solution was transferred to a polytetrafluoroethylene liner and loaded into a hydrothermal reactor and reacted at 180°C for 6.5 hours; after the reaction was completed and naturally cooled, the obtained sample was centrifuged at 7000rpm for 8 minutes, the solid was collected, washed, and then dried at 60°C for 12 hours; finally, the dried material was calcined at 700°C for 2.5 hours to obtain lanthanum cobaltate microspheres.
[0041] Example 2
[0042] A method for preparing an antibacterial ceramic glaze comprises the following steps:
[0043] (1) 30 parts by weight of bentonite, 28 parts by weight of potassium feldspar, 16 parts by weight of quartz, 6 parts by weight of barium carbonate, 3.5 parts by weight of aluminum hydroxide, and 9 parts by weight of zircon are mixed and added into a ball mill, and the mixture is ball milled at a ball mill speed of 200 r / min for 4 h, and passed through a 300-mesh sieve to obtain a ceramic glaze base material;
[0044] (2) Dispersing 3 parts by weight of lanthanum cobaltate microspheres in 10 parts by weight of water, ultrasonically treating for 40 min at a temperature of 50°C, an ultrasonic frequency of 40 kHz, and an ultrasonic power of 350 W, then adding 0.5 parts by weight of nano-titanium dioxide and stirring for 11 h to obtain a mixture; after uniformly mixing 2 parts by weight of nano-titanium nitride and the mixture, adding them to a ball mill and ball milling them at a ball mill speed of 300 r / min for 1.5 h; then adding a ceramic glaze base material, adjusting the slurry specific gravity to 1.4 with water, and continuing ball milling for 26 h to obtain an antibacterial ceramic glaze.
[0045] The preparation method of the lanthanum cobaltate microspheres is consistent with that in Example 1.
[0046] Example 3
[0047] A method for preparing an antibacterial ceramic glaze comprises the following steps:
[0048] (1) 30 parts by weight of bentonite, 28 parts by weight of potassium feldspar, 16 parts by weight of quartz, 6 parts by weight of barium carbonate, 3.5 parts by weight of aluminum hydroxide, and 9 parts by weight of zircon are mixed and added into a ball mill, and the mixture is ball milled at a ball mill speed of 200 r / min for 4 h, and passed through a 300-mesh sieve to obtain a ceramic glaze base material;
[0049] (2) Dispersing 3 parts by weight of lanthanum cobaltate microspheres in 10 parts by weight of water, ultrasonically treating for 40 minutes at a temperature of 50°C, an ultrasonic frequency of 40 kHz, and an ultrasonic power of 350 W, then adding 0.5 parts by weight of nano zinc oxide and stirring for 11 hours to obtain a mixture; after mixing 2 parts by weight of nano titanium nitride and the mixture evenly, adding them to a ball mill and ball milling them at a ball mill speed of 300 r / min for 1.5 hours; then adding a ceramic glaze base material, adjusting the slurry specific gravity to 1.4 with water, and continuing ball milling for 26 hours to obtain an antibacterial ceramic glaze.
[0050] The preparation method of the lanthanum cobaltate microspheres is consistent with that in Example 1.
[0051] Example 4
[0052] A method for preparing an antibacterial ceramic glaze, which differs from Example 3 in that 0.5 parts by weight of nano zinc oxide in step (2) is replaced by 0.3 parts by weight of nano zinc oxide.
[0053] Example 5
[0054] A method for preparing an antibacterial ceramic glaze, which differs from Example 3 in that 0.5 parts by weight of nano zinc oxide in step (2) is replaced by 1 part by weight of nano zinc oxide.
[0055] Comparative Example 1
[0056] A method for preparing an antibacterial ceramic glaze comprises the following steps:
[0057] (1) 30 parts by weight of bentonite, 28 parts by weight of potassium feldspar, 16 parts by weight of quartz, 6 parts by weight of barium carbonate, 3.5 parts by weight of aluminum hydroxide, and 9 parts by weight of zircon are mixed and added into a ball mill, and the mixture is ball milled at a ball mill speed of 200 r / min for 4 h, and passed through a 300-mesh sieve to obtain a ceramic glaze base material;
[0058] (2) 2 parts by weight of nano titanium nitride and 0.5 parts by weight of nano silver powder were mixed evenly and added to a ball mill, and ball milled for 1.5 hours at a ball mill speed of 300 r / min; then the ceramic glaze base material was added, the slurry specific gravity was adjusted to 1.4 with water, and the ball milling was continued for 26 hours to obtain an antibacterial ceramic glaze.
[0059] Comparative Example 2
[0060] A method for preparing an antibacterial ceramic glaze, which differs from Comparative Example 1 in that 0.5 parts by weight of nano silver powder is replaced by 0.5 parts by weight of nano titanium dioxide.
[0061] Comparative Example 3
[0062] A method for preparing an antibacterial ceramic glaze, which differs from Comparative Example 1 in that 0.5 parts by weight of nano silver powder is replaced by 0.5 parts by weight of nano zinc oxide.
[0063] Comparative Example 4
[0064] A method for preparing an antibacterial ceramic glaze comprises the following steps:
[0065] (1) 30 parts by weight of bentonite, 28 parts by weight of potassium feldspar, 16 parts by weight of quartz, 6 parts by weight of barium carbonate, 3.5 parts by weight of aluminum hydroxide, and 9 parts by weight of zircon are mixed and added into a ball mill, and the mixture is ball milled at a ball mill speed of 200 r / min for 4 h, and passed through a 300-mesh sieve to obtain a ceramic glaze base material;
[0066] (2) 2 parts by weight of nano titanium nitride and 3 parts by weight of lanthanum cobaltate microspheres were mixed evenly and added to a ball mill, and ball milled for 1.5 hours at a ball mill speed of 300 r / min; then the ceramic glaze base material was added, the slurry specific gravity was adjusted to 1.4 with water, and the ball milling was continued for 26 hours to obtain an antibacterial ceramic glaze.
[0067] The preparation method of the lanthanum cobaltate microspheres is consistent with that in Example 1.
[0068] Comparative Example 5
[0069] A method for preparing an antibacterial ceramic glaze comprises the following steps:
[0070] (1) 30 parts by weight of bentonite, 28 parts by weight of potassium feldspar, 16 parts by weight of quartz, 6 parts by weight of barium carbonate, 3.5 parts by weight of aluminum hydroxide, and 9 parts by weight of zircon are mixed and added into a ball mill, and the mixture is ball milled at a ball mill speed of 200 r / min for 4 h, and passed through a 300-mesh sieve to obtain a ceramic glaze base material;
[0071] (2) Dispersing 3 parts by weight of lanthanum cobaltate microspheres in 10 parts by weight of water, ultrasonically treating the mixture for 40 min at a temperature of 50°C, an ultrasonic frequency of 40 kHz, and an ultrasonic power of 350 W, then adding 0.5 parts by weight of nano zinc oxide and stirring for 11 h to obtain a mixture; adding the mixture to a ball mill and ball milling it at a ball mill speed of 300 r / min for 1.5 h; then adding a ceramic glaze base material, adjusting the slurry specific gravity to 1.4 with water, and continuing ball milling for 26 h to obtain an antibacterial ceramic glaze.
[0072] The preparation method of the lanthanum cobaltate microspheres is consistent with that in Example 1.
[0073] Test Example 1
[0074] Antibacterial performance test
[0075] The antibacterial properties of the antibacterial ceramic glazes prepared in Examples 1-5 and Comparative Examples 1-4 were tested in the following manner:
[0076] The antibacterial ceramic glazes prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 were respectively and evenly coated on the surface of the blank by a dipping method, and the thickness of the glaze layer was 1 mm. The blank was dried to obtain a glazed daily-use ceramic body. The glazed daily-use ceramic body was placed in a kiln, and the temperature was raised to 1250±10°C at a heating rate of 20°C / min, and the firing time was 8 hours. After keeping warm, the blank was naturally cooled to obtain a finished antibacterial ceramic.
[0077] The green body is a conventional commercially available ceramic body.
[0078] According to the standard "JC / T 897-2014 Antibacterial Performance of Antibacterial Ceramic Products", the antibacterial properties of the antibacterial ceramic glazes prepared in Examples 1-5 and Comparative Examples 1-4 were tested for 24 hours without light, under sunlight and under daily household light, using Escherichia coli AS1.90 and Staphylococcus aureus AS1.89 as test strains.
[0079] The test results of the antibacterial properties of the antibacterial ceramic glazes prepared in Examples 1-5 and Comparative Examples 1-4 are shown in Table 1 below:
[0080] Table 1 Test results of antibacterial properties of ceramic glazes
[0081]
[0082]
[0083] From the data in Table 1, it can be seen that the antibacterial ceramic glazes in Examples 1-5 all showed good antibacterial properties, especially under sunlight and light, the antibacterial rates of Escherichia coli and Staphylococcus aureus were generally higher than 90%, which shows that the composite use of lanthanum cobaltate microspheres and different nanomaterials can effectively improve the antibacterial effect of antibacterial ceramic glazes. Among them, the antibacterial rate of Escherichia coli in Example 3 under sunlight reached 99.3%, and the antibacterial rate of Staphylococcus aureus reached 98.5%, with the best antibacterial effect. The reason for this may be that under high temperature conditions, the precursor mixture of lanthanum cobaltate microspheres (LaCoO3) and nano zinc oxide (ZnO) was heated to a certain temperature, causing the two materials to melt or dissolve, resulting in La 3+ Ions and Zn 2+ The electrostatic interaction between ions is weakened, the ion mobility is enhanced, and La 3+ions may move from the LaCoO3 lattice, and Zn 2+ The ions may move from the ZnO lattice, and the two undergo ion exchange, resulting in La 3+ and Zn 2+ The ratio of ions changes, forming a new solid solution, thus forming a LaCoO3 / ZnO composite with a new crystal structure, which may be more conducive to the release of antibacterial ions, thereby enhancing the antibacterial performance. In addition, ZnO has photocatalytic activity and can produce reactive oxygen species (ROS) under light, which can destroy the cell structure of bacteria and cause bacterial death.
[0084] In LaCoO3 / ZnO composites, the photocatalytic effect of the composites is enhanced by the synergistic effect of LaCoO3 and ZnO. Under light conditions, photogenerated electrons and holes, as well as active oxygen species such as hydroxyl radicals (·OH) and superoxide anions (·O) can be more effectively generated. 2- ), these ROS can directly oxidize bacterial cell membranes and proteins, destroying the structure and function of bacteria. 3+ Ions and Zn 2+ The ions produce lattice movement and ion exchange, which may broaden the light absorption range of the material, enabling it to absorb a wider spectrum including ultraviolet light and visible light, causing the LaCoO3 / ZnO composite material to respond to visible light in addition to ultraviolet light, enhancing the photocatalytic activity of the material and further increasing its antibacterial effect under light.
[0085] In addition, LaCoO3 and ZnO form a LaCoO3 / ZnO composite with a new crystal structure under high temperature conditions. The porous structure of lanthanum cobalt oxide microspheres forms a wrapping layer for nano-zinc oxide, which exhibits higher thermal stability at high temperatures. The LaCoO3 / ZnO composite may have a more stable lattice structure than ZnO or LaCoO3 alone, and is not easily destroyed at high temperatures, thereby protecting Zn 2+ ions, maintaining its antibacterial activity. 2+ ions may be fixed in the new lattice structure, thus limiting the Zn 2+ The thermal movement reduces the ion volatilization or loss caused by high temperature, which can protect Zn 2+ The ions are active in high temperature environments and maintain a high antibacterial effect.
[0086] By comparing Examples 1-2 and Examples 3-5, it was found that the antibacterial performance of Example 3-5, in which lanthanum cobaltate microspheres were combined with nano-zinc oxide, was significantly better than that of Example 1, in which lanthanum cobaltate microspheres were combined with nano-silver powder, and Example 2, in which lanthanum cobaltate microspheres were combined with nano-titanium dioxide. The reason for this may be that compared with nano-titanium dioxide, the photocatalytic activity of nano-titanium dioxide mainly depends on ultraviolet light, while nano-zinc oxide can respond not only to ultraviolet light but also to visible light, which enables nano-zinc oxide to maintain a high antibacterial activity under natural light or indoor lighting conditions; compared with nano-silver powder, nano-zinc oxide can respond to ultraviolet light and visible light, which enables it to function under sunlight or indoor lighting, and although nano-silver powder can also carry out photocatalytic reactions, its spectral response may not be as wide as that of nano-zinc oxide, limiting its performance under visible light.
[0087] Comparing Example 4 and Example 5, it was found that the antibacterial effect decreased when the amount of nano zinc oxide was reduced from 0.5 parts by weight to 0.3 parts by weight and increased to 1 part by weight, which indicates that the amount of nano zinc oxide has a certain influence on the antibacterial performance. Excessive nano zinc oxide will completely wrap the lanthanum cobaltate microspheres, which is not conducive to the response of the composite to light; a small amount cannot achieve the best antibacterial effect.
[0088] Comparing Examples 1-5 and 1-4, it is found that the antibacterial rate of Example 1-3 is less than 80%, the antibacterial rate of Example 4 is less than 40%, and the antibacterial effect of Example 1-4 does not change significantly under light and light. Compared with Examples 1-5, in Example 1-3, even if traditional antibacterial additives such as nano silver powder, nano titanium dioxide, and nano zinc oxide are used, due to the lack of lanthanum cobaltate microspheres used in conjunction with them, the antibacterial additives lose protection during the high-temperature sintering process, and ions may volatilize or run off due to high temperature, causing the material to lose some antibacterial activity, resulting in a decrease in the final antibacterial effect of the material; although the lanthanum cobaltate microspheres in Example 4 show good ultraviolet-visible absorption characteristics, show photocatalytic activity under light, produce active oxygen species, and then cause bacterial death, and have a certain antibacterial effect, the antibacterial effect is poor because no antibacterial additives are used.
[0089] In summary, through the composite strategy of nano-titanium nitride and lanthanum cobaltate microspheres with antibacterial additives nano-silver powder, nano-titanium dioxide, and nano-zinc oxide, lanthanum cobaltate microspheres are composited with nano-silver powder, nano-titanium dioxide, and nano-zinc oxide to form a complex with a new crystal structure, which can not only protect the activity of the antibacterial material at high temperature and maintain excellent antibacterial effect, but also solve the problem that the antibacterial effect of traditional antibacterial additives is easily reduced at high temperature, and has better photocatalytic antibacterial effect.
[0090] Test Example 2
[0091] Thermal shock resistance test
[0092] The thermal shock resistance of the antibacterial ceramic glazes prepared in Examples 3-5 and Comparative Examples 4-5 was tested by the following specific method:
[0093] The antibacterial ceramic glazes prepared in Examples 3-5 of the present invention and Comparative Examples 4-5 are respectively and evenly coated on the surface of the blank by a dipping method, and the thickness of the glaze layer is 1 mm. The blank is dried to obtain a glazed daily-use ceramic body. The glazed daily-use ceramic body is placed in a kiln, and the temperature is increased to 1250±10°C at a heating rate of 20°C / min, and the firing time is 8 hours. After keeping warm, the blank is naturally cooled to obtain a finished antibacterial ceramic.
[0094] The green body is a conventional commercially available ceramic body.
[0095] According to the standard "GB / T 3298-2022 Test Method for Thermal Shock Resistance of Daily-use Ceramics", the finished antibacterial ceramics made of the antibacterial ceramic glazes prepared by the above-mentioned Examples 3-5 and Comparative Examples 4-5 of the present invention were tested for thermal shock resistance. During the test, the test sample was heated to 400°C and then put into 20°C water, and the test was repeated three times to observe the cracks. Among them, the number of samples set for each test example was 8, and the samples were free of cracks and damage.
[0096] The test results are shown in Table 2 below.
[0097] Table 2 Test results of thermal shock resistance of ceramic glazes
[0098]
[0099] As shown in Table 2, in comparison of Examples 3-5 and Comparative Examples 4-5, nano zinc oxide, nano titanium nitride and lanthanum cobaltate microspheres were added in Examples 3-5, and these samples performed well in the thermal shock resistance test, and all samples were free of cracks and damage; in Comparative Example 4, nano zinc oxide was not added, but nano titanium nitride and lanthanum cobaltate microspheres were directly mixed with the ceramic glaze base material, and cracks appeared in 2 samples; in Comparative Example 5, nano titanium nitride was not added, but nano zinc oxide and lanthanum cobaltate microspheres were directly mixed with the ceramic glaze base material, but in the thermal shock resistance test, cracks appeared in 4 samples. The reason for this may be that during the high-temperature calcination process, nano titanium nitride may form a composite material with a lower thermal expansion coefficient with zircon in the ceramic glaze base material, which can improve the thermal shock resistance of the ceramic material, so that the ceramic can withstand rapid changes in temperature without breaking. However, due to the high temperature and long time during the ceramic calcination process, nano-titanium nitride will agglomerate, affecting the composite of nano-titanium nitride and zircon, and may cause uneven dispersion in the glaze, which may form stress concentration points during the firing process, leading to cracks and affecting the thermal shock resistance of the ceramic. Lanthanum cobaltate microspheres can hinder the aggregation of nano-titanium nitride particles to a certain extent due to their porous structure, thereby playing a dispersing role, and the addition of lanthanum cobaltate microspheres may form a certain steric hindrance between nano-titanium nitride particles. This steric hindrance can prevent close contact between particles, thereby reducing the occurrence of agglomeration, avoiding the adverse effects of agglomeration on the thermal shock resistance of ceramic materials, and improving their thermal stability. In addition, nano-zinc oxide forms a LaCoO3 / ZnO complex with a new crystal structure with lanthanum cobaltate microspheres during high-temperature calcination, which may have different thermal expansion behaviors. By adjusting or optimizing the thermal expansion coefficient of the glaze to make it closer to the thermal expansion coefficient of the ceramic matrix, it is helpful to enhance the thermal shock resistance of the ceramic glaze.
Claims
1. A method for preparing an antibacterial ceramic glaze, characterized in that: The following steps are involved: (1) mixing bentonite, potassium feldspar, quartz, barium carbonate, aluminum hydroxide and zircon uniformly, adding the mixture into a ball mill, ball milling and sieving to obtain a ceramic glaze base material; (2) dispersing lanthanum cobaltate microspheres in water, ultrasonically treating, then adding an antibacterial additive, stirring for 10-12 hours to obtain a mixture; mixing nano titanium nitride and the mixture evenly, adding the mixture to a ball mill, and ball milling; then adding a ceramic glaze base material, adjusting the slurry specific gravity with water, and continuing ball milling to obtain an antibacterial ceramic glaze; The weight proportion of each raw material component is: 25-35 parts of bentonite, 25-35 parts of potassium feldspar, 15-20 parts of quartz, 5-8 parts of barium carbonate, 3-5 parts of aluminum hydroxide, 8-10 parts of zircon, 1.5-3 parts of nano titanium nitride, 2-5 parts of lanthanum cobaltate microspheres, and 0.3-1 parts of antibacterial additives; The preparation method of the lanthanum cobaltate microspheres comprises the following steps, measured by weight: 0.14-0.3 parts of lanthanum (III) nitrate hexahydrate, 0.1-0.2 parts of cobalt (II) nitrate hexahydrate, and 35-45 parts of isopropanol are mixed and stirred for 30-40 minutes until the mixture is uniformly mixed, and then 6-10 parts of propylene glycol are added and ultrasonically treated for 30-40 minutes to obtain a mixed solution; the mixed solution is transferred to a polytetrafluoroethylene liner and placed in a hydrothermal reactor to react at 170-200° C. for 6-10 hours; after the reaction is completed and cooled naturally, the obtained sample is centrifuged at 6000-8000 rpm for 5-10 minutes, the solid is collected, washed, and then dried at 55-65° C. for 10-15 hours; finally, the dried material is calcined at 650-750° C. for 2-3 hours to obtain lanthanum cobaltate microspheres; The antibacterial additive is selected from one of nano zinc oxide, nano silver powder and nano titanium dioxide.
2. The method for preparing the antibacterial ceramic glaze according to claim 1, characterized in that: In the step (1), the ball milling is performed at a ball milling speed of 150-250 r / min for 3-5 hours; and the sieving is performed through a 300-400 mesh sieve.
3. The method for preparing the antibacterial ceramic glaze according to claim 1, characterized in that: In the step (2), the temperature of the ultrasonic treatment is 40-60°C, the ultrasonic frequency is 30-50KHz, the ultrasonic power is 300-400W, and the time is 30-50min.
4. The method for preparing the antibacterial ceramic glaze according to claim 1, characterized in that: In the step (2), the nano titanium nitride and the mixture are mixed evenly and then added into a ball mill, and ball milled for 1-2 hours at a ball mill speed of 250-350 r / min.
5. The method for preparing the antibacterial ceramic glaze according to claim 1, characterized in that: In the step (2), ceramic glaze base material is added, the slurry specific gravity is adjusted to 1.2-1.6 with water, and ball milling is continued at a ball milling speed of 250-350 r / min for 25-30 hours.
6. An antibacterial ceramic glaze, characterized in that: Prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
A ceramic glaze with antibacterial function, its preparation method and application
CN113860734B
Preparation method of composite ceramic material
CN108640650A
Antibacterial digital glaze for ink-jet printing, preparation method and functional ceramic
CN111732339A
Self-assembled lanthanum cobaltate microsphere / silver phosphate nano-composite photo-responsive antibacterial agent as well as preparation method and application of self-assembled lanthanum cobaltate microsphere / silver phosphate nano-composite photo-responsive antibacterial agent
CN116060050A
Antibacterial domestic ceramic cup and preparation method thereof
CN116751031A